Hepatic dysfunctions in COVID-19 patients infected by the omicron variant of SARS-CoV-2 - Zhang, Jianguo; Zhao, Daguo; Hu, Jianhui; Huang, Xing; Gu, Qingqing; Tao, Zhimin (Frontiers in Public Health, 2022)
Abstract Background: While the omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) becomes dominant amid the coronavirus disease 2019 (COVID-19) pandemic, its clinical characteristics with intrinsic severity and organ tropism remain understudied. Methods: We reported 1001 COVID-19 patients that were infected with the omicron variant of SARS-CoV-2 and hospitalized in Jiangsu Province, China, from February to June 2022, with their demographic information, medical/immunization history, clinical symptom, and hematological profile. Patients with one-, two- and three-dose vaccination were compared to assess the vaccine effectiveness. Moreover, liver damage caused by the omicron variant was estimated, in comparison to that caused by the wild-type or the delta variant SARS-CoV-2. Results: For the mild COVID-19 patients, their median age was 36.0 [interquartile range (IQR): 26.0-50] and 50.3% were male. Hypertension, diabetes, and bronchitis were the leading comorbidities. Asymptomatic patients took up a major portion (61.2%). For hematological parameters, most values revealed the alleviated pathogenicity, while full vaccination or booster shot showed an effective protection against clinical severity. Conclusions: Our results supported that the viremic effect of the omicron variant tends to be modest, while the liver damage caused by this strain became milder than the previous circulating variants.